Preparation of high concentration dispersions of exfoliated MoS 2 with increased flake size - COLEMAN, JONATHAN NESBIT; O'NEILL, ARLENE; KHAN, UMAR (My University, 2012)
Solvent exfoliation of inorganic layered compounds is likely to be important for a range of applications. However, this method generally gives dispersions of small nanosheets at low concentrations. Here we describe methods, based on sonication of powdered MoS2 in the solvent N-methyl-pyrrolidone, to prepare dispersions with significantly increased lateral nanosheet size and dispersed concentration. We find the concentration to scale linearly with starting MoS2 mass allowing the definition of a yield. This yield can be increased to ~40% by controlling the sonication time, resulting in concentrations as high as 40 mg/ml. We find the nanosheet size to increase initially with sonication time reaching ~700 nm (for a concentration of ~7.5 mg/ml). At longer sonication times the nanosheets size falls off due to sonication induced scission. The nanosheets produced by such methods are relatively thin and have no observable defects. We can separate the dispersed nanosheets by size using controlled centrifugation. This allows us to produce dispersions with mean flake size of up to ~2? m. However, such large flakes are noticeably thicker than the standard nanosheets. We demonstrate that such nanosheets can be mixed with polymers to form composites. While standard nanosheets result in no improvement in composite mechanical properties, addition of size-selected nanosheets results in significant improvements in composite modulus and strength.
PUBLISHED
Keywords: layered compound, exfoliation, two dimensional, dispersion, nanosheets, composite; layered compound, exfoliation, two dimensional, dispersion, nanosheets, composite